METHODOLOGY OF INTERACTIVE INTERACTION OF MODERN MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS IN GLOBALIZATION PROCESSES - PhD Soxibov Akram Rustamovich (Galaxy International Interdisciplinary Research Journal, 2024)
The processes of managing of innovative development in higher educational institutions in the conditions of formation of innovative economy, the roles of managers of the institutions, approaches to the management of the higher educational system in the process of globalization, and experiences of foreign countries in this field have been described in the article. Also, the analysis of the activity of management of innovative, scientific-pedagogical and scientific research processes in higher educational institutions has been carried out. It has been attempted to develop some suggestions and recommendations for Monitoring of conflict situations in the management of innovative development processes in higher education, increasing the effectiveness of leaders’ participation in the process of innovative development using technologies of resolving them.